2010
DOI: 10.3109/02813432.2010.514191
|View full text |Cite
|
Sign up to set email alerts
|

Considerations made by the general practitioner when dealing with sick-listing of patients suffering from subjective and composite health complaints

Abstract: (2011) Considerations made by the general practitioner when dealing with sicklisting of patients suffering from subjective and composite health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 19 publications
9
67
0
6
Order By: Relevance
“…The most central aspect of physicians' sickness certification tasks is to determine whether a patient has a disease, and to assess the degree to which this disease reduces the patient's functioning and in relation to work demands and work tasks, the patient's ability to work [3]. Our results support previous findings regarding the problems of assessing work ability, especially when clinical findings are missing [9,13,16,5], but also reveal that the presence of psychological, social, or work-related factors aggravate the assessments. The finding that physicians primarily base their assessments on a feeling of trust in the information given by the patient agrees with earlier research [16,21,18].…”
Section: Work Ability Assessmentssupporting
confidence: 82%
See 2 more Smart Citations
“…The most central aspect of physicians' sickness certification tasks is to determine whether a patient has a disease, and to assess the degree to which this disease reduces the patient's functioning and in relation to work demands and work tasks, the patient's ability to work [3]. Our results support previous findings regarding the problems of assessing work ability, especially when clinical findings are missing [9,13,16,5], but also reveal that the presence of psychological, social, or work-related factors aggravate the assessments. The finding that physicians primarily base their assessments on a feeling of trust in the information given by the patient agrees with earlier research [16,21,18].…”
Section: Work Ability Assessmentssupporting
confidence: 82%
“…Our results support previous findings regarding the problems of assessing work ability, especially when clinical findings are missing [9,13,16,5], but also reveal that the presence of psychological, social, or work-related factors aggravate the assessments. The finding that physicians primarily base their assessments on a feeling of trust in the information given by the patient agrees with earlier research [16,21,18]. In line with a previous study [16], we found that the patient's ability to evoke empathy and describe his or her symptoms and working conditions played an important role in obtaining the sickness certification.…”
Section: Work Ability Assessmentssupporting
confidence: 82%
See 1 more Smart Citation
“…Research suggests that healthcare practitioners may dislike patients when clear medical evidence for the pain is lacking. 57,62 Further, healthcare providers may have more doubts about the genuineness of the pain symptoms 38,40,43 when pain has no clear medical explanation.…”
Section: Journal Of Pain -Accepted Uncorrected Manuscriptmentioning
confidence: 99%
“…Attributing lower pain and disability to patients may impact treatment decisions and may lead to inadequate pain management. Nilsen and colleagues 43 found that patients with symptoms for which there was no clear biomedical basis were at risk of not receiving certificates attesting to their being ill. Moreover, healthcare practitioners may be perceived by patients as invalidating their pain complaints, leading to perceived injustice and exacerbating the disability.…”
mentioning
confidence: 99%